Detection and analysis of stress-induced voiding in Al-power lines by acoustic GHz-microscopy. (September 2016) - Brand, S.; Simon-Najasek, M.; Kögel, M.; Jatzkowski, J.; Portius, R.; Altmann, F.
Abstract: The formation of voids in metal layers upon stress-induced migration is a well-known defect mechanism in integrated circuits. This phenomenon largely accelerates with increasing ambient temperature. Consequently, the occurrence and the growth of voids result in an increased electrical resistivity which once more leads to an acceleration of the growth rate highly impacting the reliability and the life span of the device. Technological improvements aim at the minimization of stress induced voiding. However, for understanding and optimization of process related factors non-destructive methods for screening and systematic monitoring of the void formation e.g. during stepwise reliability testing are required. In the current paper, the formation of voids induced by repetitive thermal loads has been assessed and evaluated semi-destructively by employing Scanning Acoustic GHz-Microscopy. Prior to the acoustic inspection, sophisticated semi-destructive preparation was required to provide access to the region of interest. Voids with sizes below the acoustic resolution limit have been detected. The relative number and the size of appearance have been analysed using a custom made analysis software tool. Highlights: The current paper employs acoustic GHz-microscopy for inspection sub-micron sized stress voids in AlCu metallization systems. Void formation of samples receiving temperature cycling was compared to untreated samples. Two sets of stressed samples were investigated: one set contained a TiN interlayer while the other one only consisted of AlCu.